Elaborate the Superiority of Smart City in South Korea: A Study Comparison of Laws - Sudirman, Lu; Disemadi, Hari Sutra; Manurung, Kevin John Paul (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
The advancement of technology has played a significant role in societal life, providing convenience across various aspects and creating practical solutions. One phenomenon emerging alongside this progress is the Internet of Things (IoT), a concept of continuous connectivity within networks. A massive implementation of IoT is seen in the concept of Smart City, which integrates this technology to efficiently enhance the quality of life for communities. This research aims to compare the legal regulations governing Smart Cities in South Korea and Indonesia. In Indonesia, there is currently no specific legal regulation for Smart Cities, making a comparison with South Korea particularly valuable. The research methodology employed is normative legal research, utilizing secondary data obtained through literature studies, focusing on legislative analysis and a comparative approach. The findings of this research provide an elaboration on the comparison of legal regulations for Smart Cities in Indonesia and South Korea. The research results are also accompanied by recommendations for the establishment of Smart City legal regulations that could be utilized at the national level.